Building Meaningful Education: Integrating Islamic Values in English Language Teaching At Mts Ash-Shalihin - Nurpahmi, Sitti; Nur, Nur Aliyah; Amsar, Asriani; Rezky, Putri Ananda; Fajriah, Suci; Nabila, Kaisan (IJOCSE: Indonesian Journal of Community Services, 2023)
Abstract: This article explores the integration of Islamic values in English language teaching at MTs Ash-Shalihin. The study employed qualitative research methods, including interviews, observations, and document analysis. The findings reveal that incorporating Islamic values in the classroom enhances students' understanding of their faith and proficiency in English. Teachers utilize strategies such as selecting appropriate teaching materials, incorporating Islamic principles into lessons, and fostering a supportive learning environment. The integration of Islamic values positively impacts students' character development and motivation. However, the study also highlights the need for teacher training and adequate instructional resources. Overall, this research underscores the importance of combining Islamic values with English language instruction to foster a meaningful educational experience at MTs Ash-Shalihin.